2021
DOI: 10.7717/peerj.11598
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short-term grazing prohibition on soil physical and chemical properties of meadows in Southwest China

Abstract: Background Grassland plays an important role in the ecosystem, but overgrazing harms the grassland system in many places. Grazing prohibition is an effective method to restore grassland ecosystems, and it plays a great role in realizing the sustainable development of grassland systems. Therefore, it is necessary to carry out research on the influence of regional grazing prohibition on the physical and chemical properties of different grassland systems. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
(128 reference statements)
1
4
0
Order By: Relevance
“…Different habitat conditions were the key factors that controlled the influences of GE on carbon storage between alpine meadow and alpine steppe, with more carbon could be accumulated in relatively humid regions (alpine meadow) than that in the relatively arid regions (alpine steppe) (Su and Xu, 2021;Sun et al, 2020b). Both in the alpine meadow and alpine steppe, GE was more effective in promoting AGB than BGB (Figure 2A), which is consistent with other studies (Xiong et al, 2014;Hong et al, 2015;Zhu et al, 2021). According to previous studies, plants would allocate more biomass to belowground parts to minimize the loss caused by grazing (Diaz et al, 2007;Yan et al, 2013).…”
Section: Responses Of Carbon Fractions To Ge In Alpine Grasslandssupporting
confidence: 89%
See 1 more Smart Citation
“…Different habitat conditions were the key factors that controlled the influences of GE on carbon storage between alpine meadow and alpine steppe, with more carbon could be accumulated in relatively humid regions (alpine meadow) than that in the relatively arid regions (alpine steppe) (Su and Xu, 2021;Sun et al, 2020b). Both in the alpine meadow and alpine steppe, GE was more effective in promoting AGB than BGB (Figure 2A), which is consistent with other studies (Xiong et al, 2014;Hong et al, 2015;Zhu et al, 2021). According to previous studies, plants would allocate more biomass to belowground parts to minimize the loss caused by grazing (Diaz et al, 2007;Yan et al, 2013).…”
Section: Responses Of Carbon Fractions To Ge In Alpine Grasslandssupporting
confidence: 89%
“…Specifically, in terms of plant biomass, some studies observed that GE increased the aboveground biomass (AGB) (Liu and Nie, 2012;Yang et al, 2017) and the belowground biomass (BGB) (Du and Gao, 2021;Wang F, et al, 2020), while other studies found that GE could have a relatively neutral effect on AGB (Yuan et al, 2020) or negative impacts on AGB (Yan et al, 2014) and BGB (Wu et al, 2021). A previous study observed that short-term GE increased AGB but decreased BGB in the alpine meadow (Zhu et al, 2021). Other studies found that AGB increased and then decreased (Chen et al, 2019), BGB decreased and then increased (Hong et al, 2015) with the extension of GE duration across the alpine steppe.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the soil nitrogen cycle was also affected, and soil bulk density and soil organic matter content decreased, which reduced the plant density and species richness of the grassland. The long-term grazing ban will lead to the degradation of grassland vegetation and soil nutrients [40,41]. It follows that the optimal prohibition time may vary under different conditions [42].…”
Section: Ecological Problems In the Suhai Lake Basin From The Perspec...mentioning
confidence: 99%
“…In New Zealand, for example, substantial areas of alpine tall tussock grasslands have been restricted from grazing to reduce the negative impact on the ecosystem (Norton & Young, 2016). In northern China, the “grazing exclusion” policy has been implemented on severely degraded grasslands since the early 1990s to curb the degradation (Tai et al, 2021; Zhu et al, 2021). In southeastern Australia, best management practices have been implemented for decades to naturally recover deteriorated grasslands due to animal treading, which substantially improved physical properties of the soil, such as hydraulic conductivity, macropore volume, and bulk density (Drewry, 2006).…”
Section: Introductionmentioning
confidence: 99%